FACTORS INFLUENCING RESIDENTIAL PROPERTY PURCHASE DECISIONS DURING THE COVID-19 PANDEMIC (CASE STUDY ON CITRALAND GAMA CITY MEDAN HOUSING) - F. X. Ery Kristiono,; Elisabet Siahaan,; Nazaruddin, Nazaruddin (Journal of Innovation Research and Knowledge, 2022)
The purpose of this research is to understand factors influencing residential property purchase decisions during the COVID-19 pandemic, case study on Citraland Gama City Medan Housing. Research in this study using quantitative research. The population in this study are 251 heads of families who are all property buyers of Citraland Gama City Medan Housing during the COVID-19 pandemic. The sample in this study are 72 heads of families who are all property buyers of Citraland Gama City Medan Housing during the COVID-19 pandemic. Testing the hypothesis in research using a partial test (t). The results of the study show that product has a positive and significant effect on residential property purchase decisions during the COVID-19 pandemic. Price has a positive and significant effect on residential property purchase decisions during the COVID-19 pandemic. Promotion has a positive and insignificant effect on residential property purchase decisions during the COVID-19 pandemic. Location has a positive and insignificant effect on residential property purchase decisions during the COVID-19 pandemic. People has a positive and insignificant effect on residential property purchase decisions during the COVID-19 pandemic. Physical evidence has a positive and significant effect on residential property purchase decisions during the COVID-19 pandemic.